BUDAYA POPULER GAME POKEMON GO SEBAGAI SOFT DIPLOMACY JEPANG - Iqbal, Chadijah Isfariani (Universitas Diponegoro, 2016)
Pokemon Go is a smartphone game that blends the real and digital worlds, tasking players with exploring their neighborhoods to find creatures and treasure for in-game use. This research describes the ways Japan uses its soft power in international coorporation relations, particulary through Pokemon Go’s game. Based on Joseph S. Nye, Jr, the soft power defined as the ability of country to achieve its goal using cultural attraction rather than coercion and violence. After the World War II, Japan has tried to change its image as war crime through popular culture, such as anime, manga and cosplay. According to Nye, Japan has more potential resources in soft power compared to the other countries. This research is focus on Popular Culture of Pokemon Go’s Game as Japan’s Soft Diplomacy. Pokemon Go is one of Japan’s cultural diplomacy activities and the other countries uses popular culture to strengthen the positive image of Japan in the international world. The development of popular culture as a soft power and soft diplomacy also a diplomacy tool of development that can be used by Japan in conducting foreign policy in relation to international cooperation. <a href=